Brain-Computer Interface: A Revolutionary Technology Expanding the Frontiers of the Human Brain and the Future of Neurosurgery - ZHAO Jizong (Xiehe Yixue Zazhi)
The brain-computer interface (BCI) is not merely an advanced technology but also represents a profound revolution spanning neuroscience, artificial intelligence, computer science, philosophy, and sociology. The core value of BCI lies in its ability to break through the informational barriers between the brain and the external world, endowing humans with novel capabilities for information interaction and propelling the evolution of an intelligent society. As a disruptive technological innovation, BCI fundamentally alters the way humans interact with the world, and its applications will profoundly influence our understanding of cognition, consciousness, and even self-existence. For neurosurgery, BCI is not only a revolutionary therapeutic tool but also an opportunity to reshape traditional medical paradigms. From repairing neural damage to modulating brain functions, from enhancing human intelligence to shaping the future of human-machine integration, BCI offers unprecedented possibilities for neurosurgery. The development of this technology not only aids in a deeper understanding of brain functions but also provides robust support for future intelligent healthcare. The impact of BCI extends far beyond medicine, influencing the transformation of future computing paradigms, the proliferation of intelligence augmentation, the scrutiny of social ethics, the deployment of national strategies, the dynamics of economic development, and the safeguarding of national security.